A Plurizyme with Transaminase and Hydrolase Activity Catalyzes Cascade Reactions. (4th August 2022) - Roda, Sergi; Fernandez‐Lopez, Laura; Benedens, Marius; Bollinger, Alexander; Thies, Stephan; Schumacher, Julia; Coscolín, Cristina; Kazemi, Masoud; Santiago, Gerard; Gertzen, Christoph G. W.; Gonzalez‐Alfonso, Jose L.; Plou, Francisco J.; et al.
Abstract: Engineering dual‐function single polypeptide catalysts with two abiotic or biotic catalytic entities (or combinations of both) supporting cascade reactions is becoming an important area of enzyme engineering and catalysis. Herein we present the development of a PluriZyme, TR2 E2, with efficient native transaminase ( k cat : 69.49±1.77 min −1 ) and artificial esterase ( k cat : 3908–0.41 min −1 ) activities integrated into a single scaffold, and evaluate its utility in a cascade reaction. TR2 E2 (pHopt : 8.0–9.5; T opt : 60–65 °C) efficiently converts methyl 3‐oxo‐4‐(2, 4, 5‐trifluorophenyl)butanoate into 3‐( R )‐amino‐4‐(2, 4, 5‐trifluorophenyl)butanoic acid, a crucial intermediate for the synthesis of antidiabetic drugs. The reaction proceeds through the conversion of the β‐keto ester into the β‐keto acid at the hydrolytic site and subsequently into the β‐amino acid (e.e. >99 %) at the transaminase site. The catalytic power of the TR2 E2 PluriZyme was proven with a set of β‐keto esters, demonstrating the potential of such designs to address bioinspired cascade reactions. Abstract : A PluriZyme with transaminase and esterase activities was constructed by combining computational and laboratory design methods. The enzyme can perform cascade reactions in a single protein scaffold. Experimental evidence is presented for the catalytic efficiency of both the native transaminase and the artificial esterase active site and their synergistic action to transform β‐keto esters into enantiopure β‐amino acids.